Acute Mortality, Bacterial Load, and Pathology of Select Lines of Adult Rainbow Trout Challenged with Weissella sp. NC36. Issue 4 (18th October 2013) - Marancik, David P.; Welch, Timothy J.; Leeds, Timothy D.; Wiens, Gregory D.
Abstract: A challenge for improving disease resistance in fish through genetics is to understand specificity of resistance and whether selection for one pathogen alters the response to unrelated pathogenic microorganisms. Adult Rainbow Trout Oncorhynchus mykiss that had been bred for differential susceptibility to Flavobacterium psychrophilum, the causative agent of bacterial cold water disease (BCWD) and designated ARS‐Fp‐R (resistant), ARS‐Fp‐S (susceptible), and ARS‐Fp‐C (control line), as well as a pool of commercial‐stock Rainbow Trout, were intraperitoneally challenged with Weissella sp. NC36. Clinical signs, survival, and innate mechanisms affecting disease resistance were monitored over 9 d. Acute disease signs included exophthalmia associated with retrobulbar inflammation and hemorrhage, cerebral hemorrhage, and mild to moderate granulomatous pericarditis. The ARS‐Fp‐R line did not demonstrate significant survival differences over a 9‐d period compared with the ARS‐Fp‐C and ARS‐Fp‐S lines ( P ≥ 0.09) indicating that during the acute phase of disease, the resistance factors that limit BCWD do not confer cross protection against Weissella sp. NC36. The linear effect of body weight at challenge was statistically significant, as each 10‐g increase in body weight increased the hazard of death by 1% ( P = 0.02). Bacterial loads on day 3, assessed by splenic and cerebral CFU counts, did not differ between ARS‐Fp‐R and ARS‐Fp‐S trout and there was no correlation between CFU counts and body weight. These findings help elucidate the specificity of disease resistance in selectively bred lines and contribute to our understanding of disease caused by Weissella sp., a recently described pathogen found in cultured Rainbow Trout. Received June 19, 2013; accepted June 23, 2013